Optimizing Employee Performance Through Competence, Work Discipline and Work Enviroment Empirical Study : Mulyorejo Urban Village Office - Inggrid Fernandita Lestari; Ilya Farida (PT. Anagata Sembagi Education, 2025)
This study aims to identify and analyze: (1) The effect of competence, work discipline, and work environment on employee performance in Mulyorejo Urban Village, Surabaya; (2) The effect of competence on employee performance in Mulyorejo Urban Village, Surabaya; (3) The effect of work discipline on employee performance in Mulyorejo Urban Village, Surabaya; (4) The effect of work environment on employee performance in Mulyorejo Urban Village, Surabaya. This research employs a quantitative approach using a survey method. The research instrument is a questionnaire, with the sample consisting of all employees of Mulyorejo Sub-district. The validity test of the instrument uses r-count ≥ r-table, while the reliability test is conducted using Cronbach’s Alpha ≥ 0.60. Data analysis is performed using multiple linear regression. The results of the study at a 5% significance level show that: (1) competence, work discipline, and work environment simultaneously have a significant effect on employee performance, with F-count of 5.679 > 3.56 and a significance of 0.007 < 0.05; (2) competence has a significant partial effect on employee performance, with t-count of 3.192 > 2.109 and a significance of 0.005 < 0.05; (3) work discipline has a significant partial effect on employee performance, with t-count of 2.219 > 2.109 and a significance of 0.040 < 0.05; (4) the work environment does not have a significant partial effect on employee performance, with t-count of 0.232 < 2.109 and a significance of 0.819 > 0.05